2023
DOI: 10.1007/s10639-023-11756-y
|View full text |Cite
|
Sign up to set email alerts
|

A triangulation method on the effectiveness of digital game-based language learning for vocabulary acquisition

Abstract: This research aimed to explore the views of 8 th grade students on digital game-based English language learning as a foreign language (EFL). A total of 69 students between the ages of 12 and 14 participated in the study. Students' vocabulary acquisition skills were tested using a web 2.0 application called "Quizziz." The study utilized a triangulation method in which the results of a quasi-experiment and the metaphorical perceptions of the learners were obtained. The results of the tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This study confirms that the "Mandarin AR" app is highly beneficial in enhancing non-native speakers' Mandarin vocabulary development. This is consistent with previous studies which demonstrated that the AR technology has positive impacts on language learning by creating immersive and personalized language learning experiences, boosting students' motivation and increasing learning retention in the mind (Belda-Medina & Marrahi-Gomez 2023; Kazu & Kuvvetli, 2023;Mozaffari & Hamidi 2023;Shadiev & Liang 2023). Several reasons may be accounted for the significant achievement in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study confirms that the "Mandarin AR" app is highly beneficial in enhancing non-native speakers' Mandarin vocabulary development. This is consistent with previous studies which demonstrated that the AR technology has positive impacts on language learning by creating immersive and personalized language learning experiences, boosting students' motivation and increasing learning retention in the mind (Belda-Medina & Marrahi-Gomez 2023; Kazu & Kuvvetli, 2023;Mozaffari & Hamidi 2023;Shadiev & Liang 2023). Several reasons may be accounted for the significant achievement in this study.…”
Section: Discussionsupporting
confidence: 92%
“…After completing each vocabulary theme, students are provided with game-based exercises to reinforce their vocabulary knowledge (refer to Figure 3). Moreover, incorporating digital game-based exercises into vocabulary learning does not only make it enjoyable and fun but also reduces cognitive overload and motivates students to learn (Kazu & Kuvvetli, 2023).…”
Section: The Mandarin Ar Vocabulary Appmentioning
confidence: 99%
See 1 more Smart Citation
“…The study's focus on a specific language and the short-term assessment of speaking proficiency may restrict the generalizability of the findings. To address these limitations, future research endeavors should consider conducting longitudinal studies encompassing diverse linguistic contexts and a comprehensive range of language proficiency measures (Kazu & Kuvvetli, 2023). Moreover, investigations into the long-term sustainability of the observed enhancements in language proficiency and the examination of the interplay between individual learner characteristics and the effectiveness of Duolingo could offer additional insights for personalized language learning interventions (Ghafar et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Quizziz 2.0 Quizizz is an online platform for creating and playing quizzes, often used in education for interactive and gamified assessments (Kazu & Kuvvetli, 2023).…”
Section: Hostovecky (2022)mentioning
confidence: 99%